Tree diversity and composition in an area between upper hill dipterocarp forest and lower montane forest of, Jerai Forest Reserve - Mohd Ariff, Muhammad Adzim Ariff (2019)
The present study was conducted in an area located between a lower montane forest and upper hill dipterocarp forest at Jerai Forest Reserve, Kedah, Peninsular Malaysia. The purpose of the study was to determine the tree species composition, distribution, richness and diversity in this unique habitat by setting up one hectare plot. The unique structure of mixed forest between upper hill dipteropcarp forest with lower montane possessing numbers of admixture species. A total of 701 individuals belonging to 74 species, 61 genera and 41 families with diameter of 10cm and above were enumerated and identified. Importance value index (IVI) was calculated to show dominant species and the stand density also estimated. The highest IVI was recorded from family of Anacardiaceae with a total value of IVI 21.65%. Family Myrtaceae contributed the highest in stand density with a total of 125 individuals per hectare. Most of the species in Jerai FR stand dominated with the DBH classes of between 10cm to 24.9cm, a common size of trees in higher elevation forest. Shannon's index of diversity in Jerai FR gave a value of 3.68 indicating high diversity in Jerai FR. Tree composition at Jerai FR Is dominated by Myrtaceae with a total of 7 species from 2 genera. This is commonly seen for upper hill dipterocarp forest to lower montane forest in Malaysia with common genera such Syzygium and Tristaniopsis. At elevation of about 1000 to 1200m a.s.l (lower montane forest), the domination of dipterocarp species ends and replaced by species of oak (Quercus and Lithocarpus spp.) and chestnut (Castanopsis). Other genera that are also prominent in the study area include include Agathis, Dacrydium, Baeckea, Leptrospermum and Podocarpus.